Pre-Play Communication with Forgone Costly Messages: Experimental Evidence on Forward Induction - Andreas Blume; Peter H. Kriss; Roberto A. Weber (Center for Economic Studies and ifo Institute (CESifo), 2016)
We experimentally study optional costly communication in Stag-Hunt games. Prior research demonstrates that efficient coordination is difficult without a communication option but obtains regularly with mandatory costless pre-play messages. We find that even small communication costs dramatically reduce message use when communication is optional, but efficient coordination can occur with similar frequency as under costless communication. These findings can be accounted for by formalizations of forward induction that take Nash equilibrium as a reference point (such as Kohlberg and Mertens (1986) and Govindan and Wilson (2009)), while formalizations that only appeal to (higher-order) knowledge of rationality remain silent in this environment.
Keywords: 330; coordination; communication; forward induction; experiment; stag hunt